Association of Dual Sensory Impairment with Long-term Depressive and Anxiety Symptoms. (17th December 2021) - Armstrong, Nicole; Teixeira, Camila Vieira Ligo; Brenowitz, Willa; Swenor, Bonnielin; Powell, Danielle; Simonsick, Eleanor; Jones, Richard; Gendron, Colby
Abstract: Hearing (HI) and vision impairment (VI) are each independently associated with long-term depressive and anxiety symptoms, but the joint effects of both (DSI) may be associated with a greater risk of belonging to long-term chronically high depressive and anxiety trajectory classes. Multinomial logistic regression models adjusted by demographics and depressive symptoms were used to examine the associations of dual hearing (pure-tone average >25 dB) and vision impairment (impaired visual acuity and/or contrast sensitivity) with long-term depressive and anxiety symptom trajectory classes among 2, 102 participants of the Health, Aging and Body Composition Study, a cohort of older adults without mobility difficulty aged 70-79 years. An additional model evaluated the two-way interaction between DSI and social contact. Elevated depressive symptoms were defined as ≥8 on the 10-item Center for Epidemiologic Studies-Depression Scale, and anxiety symptoms were defined as present on the Hopkins Symptom Checklist. DSI was associated with increased risk of being chronically depressed (Risk Ratio, RR=1.86, 95% Confidence Interval, CI: 1.19, 2.92), not periodically depressed (RR=1.24, 95% CI: 0.91, 1.69). Those with DSI were at an increased risk of belonging to the periodically anxious (RR=1.56, 95% CI: 1.14, 2.13) and chronically anxious (RR=1.79, 95% CI: 1.02, 3.12) groups, as compared to the other groups. Single sensory impairments were not associated with increased risk of being periodically or chronically anxious. Social contact did not modify any associations. Synergistic effects between HI and VI were present. Those with DSI may be at greater risk for mood disorders, so sensory evaluations may mitigate these.